2008
DOI: 10.1159/000163042
|View full text |Cite
|
Sign up to set email alerts
|

Acceptance and Discomfort from Atraumatic Restorative Treatment in Secondary School Students in Egypt

Abstract: Objectives: To assess the level of acceptance and discomfort experienced by secondary school students when undergoing an atraumatic restorative treatment (ART) restoration. Subjects and Methods: Ninety secondary school students, aged 14 and 15 years, were included in the study. The ART restorations were prepared in 90 cavities and restored using an encapsulated high-viscosity glass ionomer. The depth of the cavities was judged from radiographs and clinically into outer, middle and inner third of dentine. Using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 35 publications
1
14
0
Order By: Relevance
“…This association was demonstrated in a study that aimed to determine the level of sensitivity related to cavity size and lesion depth, experienced by adolescents during ART cavity preparation 5 . The report of pain and discomfort was, in general, low; more frequently experienced in large than in small cavities and in cavities with the floor close to the pulp.…”
Section: Art Acceptability: Literature Evidencementioning
confidence: 95%
See 1 more Smart Citation
“…This association was demonstrated in a study that aimed to determine the level of sensitivity related to cavity size and lesion depth, experienced by adolescents during ART cavity preparation 5 . The report of pain and discomfort was, in general, low; more frequently experienced in large than in small cavities and in cavities with the floor close to the pulp.…”
Section: Art Acceptability: Literature Evidencementioning
confidence: 95%
“…In general, results retrieved from different clinical trials, conducted in different regions of the world, show that ART is well accepted both by children and by adults treated in accordance with this approach 5 , 18 , 22 . Specific methodological designs have been developed in order to demonstrate its effectiveness in terms of reducing patients' dental anxiety and causing less pain than the traditional approaches cause.…”
Section: Art Acceptability: Literature Evidencementioning
confidence: 99%
“…The successful use of ART in adolescents in Egypt is shown by the high 5-year survival rate of 85% for singlesurface ART restorations [10] and the high level of its acceptance among adolescents [11] . However, the ART study was neither accompanied by an investigation into the prevalence of dental caries among this age group, nor has the prevalence of carious lesions treatable through the ART approach been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…ART has several characteristics that make it a considered alternative for treating the elderly: reported good restoration survival rates , patient‐friendly nature and cost‐effectiveness . Mickenautsch et al.…”
mentioning
confidence: 99%
“…ART has several characteristics that make it a considered alternative for treating the elderly: reported good restoration survival rates (16,25), patient-friendly nature and cost-effectiveness (26)(27)(28). Mickenautsch et al (28) compared the use of ART to conventional techniques using amalgam and composite and found that the annual cost of ART in a dental school in South Africa was approximately 50% of the other two options.…”
mentioning
confidence: 99%